Frame synchronization algorithm based on delay-Doppler domain signal sparsity for OTFS system - CHEN Yang; YANG Haiyan; CHENG Kaiying; LIU Heng; MA Zheng (Dianxin kexue)
A frame synchronization algorithm based on delay-Doppler domain was proposed for orthogonal time frequency and space (OTFS) modulation systems with a single pilot structure. The signal sparsity and the relative position change of the pilot in the delay-Doppler domain of the received OTFS signals were utilized to identify the frame synchronization location. Simulation results were presented to demonstrate that the proposed scheme outperformed the classic synchronization scheme based on the preamble, which was commonly used in orthogonal frequency division multiplexing (OFDM) systems, in terms of lower synchronization failure rate under high signal-to-noise ratio (SNR) regions. Additionally, the proposed scheme exhibited greater performance advantages over the preamble-based scheme as the moving speed increases, making it a more suitable option for high-speed or even ultra-high-speed mobile communication scenarios.